The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0267659116679249
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection during minimally invasive cardiac surgery through right mini-thoracotomy

Abstract: Custodiol and cold blood cardioplegic solutions seem to assure similar myocardial protection in patients undergoing cardiac surgery through a right mini-thoracotomy approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In the external transthoracic clamp cases, intermittent cold blood cardioplegia has been preferred to avoid further hemodilution. We have previously demonstrated that both crystalloid and cold blood cardioplegia solutions provide adequate protection in minimally invasive cardiac surgery (10).…”
Section: Discussionmentioning
confidence: 99%
“…In the external transthoracic clamp cases, intermittent cold blood cardioplegia has been preferred to avoid further hemodilution. We have previously demonstrated that both crystalloid and cold blood cardioplegia solutions provide adequate protection in minimally invasive cardiac surgery (10).…”
Section: Discussionmentioning
confidence: 99%
“…15,36,38 Controversy concerning its use in adults does exist since the solution was initially designed for pediatric use. 39,40 Nevertheless, DN has been shown to be non-inferior to traditional CP formulations that are blood based 41,42 and is employed frequently throughout our hospital base.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, authors who have investigated outcomes following minimally invasive cardiac surgery using Custodiol-HTK solution agreed that avoiding repetitive infusions may reduce the risk for coronary malperfusion due to dislodgement of the endo-aortic clamp (if used) and increase the surgeon's comfort during the procedure. [10][11][12][13][14] Almost all the investigators who have compared Custodiol-HTK with cold blood cardioplegia have shown similar clinical outcomes for the two options. 6,9,[10][11][12]14 Actually, only a few studies have shown some benefits deriving from either one of the two cardioplegic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Almost all the investigators who have compared Custodiol-HTK with cold blood cardioplegia have shown similar clinical outcomes for the two options. 6,9,[10][11][12]14 Actually, only a few studies have shown some benefits deriving from either one of the two cardioplegic strategies. For example, lower values (p = 0.044) of cardiac troponin I for XCT >160 minutes have been reported for Custodiol-HTK patients undergoing aortic surgery by Scrascia et al 5 Prathanee et al 15 have stigmatized that by using Custodiol-HTK cardioplegia in isolated CABG there was a significantly increased risk of spontaneous ventricular fibrillation after releasing of the aortic clamp; however, no clinical significance has been given to this fact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation